Estudio de factibilidad para la creación de una microempresa productora y comercializadora de quinua (Chenopodium quinoa), chocho (Lupinus mutabilis slwet), y amaranto (Amaranthus caudatus), en el barrio Chan, parroquia Eloy Alfaro, cantón Latacunga, provincia Cotopaxi, periodo 2014-2015 - Hidalgo Moya, Jose Eduardo (2015)
The present investigative work is the result of an analysis of an entrepreneurial proposal, which basically is aimed at giving guidelines and standards for empowering the creation and constitution of a microenterprise which produce quinua, chocho and amaranth in the province of Cotopaxi, Latacunga, in the Eloy Alfaro Parish, in the Chan neighborhood. Being one of the most fundamental problems to undertake the project that Andean products are considered very nutritional food, especially rich in proteins, but there is a great inconvenient in its production and development since the high cost of the machinery limits the process. This makes producers to avoid growing it, and big producers prefer importing from other countries to meet their needs. The current production exist in the delivered sector to intermediaries, who pay low prices without letting producers obtain profitability rom it….